2020
DOI: 10.1002/open.201900335
|View full text |Cite
|
Sign up to set email alerts
|

Electrons and Hydroxyl Radicals Synergistically Boost the Catalytic Hydrogen Evolution from Ammonia Borane over Single Nickel Phosphides under Visible Light Irradiation

Abstract: From the perspective of tailoring the reaction pathways of photogenerated charge carriers and intermediates to remarkably enhance the solar‐to‐hydrogen energy conversion efficiency, we synthesized the three low‐cost semiconducting nickel phosphides Ni2P, Ni12P5 and Ni3P, which singly catalyzed the hydrogen evolution from ammonia borane (NH3BH3) in the alkaline aqueous solution under visible light irradiation at 298 K. The systematic investigations showed that all the catalysts had higher activities under visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…The abundant electrons around nickel favor the catalysis of NH 3 BH 3 hydrolysis. 27,30 The N 2 adsorption-desorption isotherm of the Fe 3 O 4 -Ni 2 P@C catalyst indicates a surface area of 72.9 m 2 g −1 with an average pore width of 13.0 nm (Fig. S17 and Table S3 †).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundant electrons around nickel favor the catalysis of NH 3 BH 3 hydrolysis. 27,30 The N 2 adsorption-desorption isotherm of the Fe 3 O 4 -Ni 2 P@C catalyst indicates a surface area of 72.9 m 2 g −1 with an average pore width of 13.0 nm (Fig. S17 and Table S3 †).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
“…18,[23][24][25] In particular, nickel phosphide, an emerging noble-metal-free catalyst, displays high activity for NH 3 BH 3 hydrolysis. 26,27 Recent reports have demonstrated that catalysts with monometallic sites can be further improved by introducing a second metal to form dual active sites. This enhancement has been attributed to the synergistic effect of dual sites during the adsorption and dissociation of NH 3 BH 3 and H 2 O molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with the UV/Vis diffuse reflectance spectra. Considering that water might interact with photogenerated electrons during the AB hydrolysis reaction to enhance the photocatalytic H 2 evolution activity, [60] CoFeÀ Mo was also tested in photocatalytic H 2 evolution from AB (Figure 7a). However, no photocatalytic H 2 evolution activity was detected.…”
Section: Catalytic Performance and Mechanismmentioning
confidence: 99%